MODEL PEMBELAJARAN BERKIRIM SALAM DAN SOAL DENGAN MEDIA BUS UNTUK MENINGKATKAN HASIL BELAJAR IPS - Setiawati, Mamik (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2016)
The purpose of this study was to determine the application of the learning model of sending greetings and questions with the BUS media to increase the activity and learning outcomes of students in class VIII A SMP Negeri 2 Tekung. There is still low student activity in preliminary observations where there are only 3 students who ask questions and 2 students who are willing to answer their friends' questions and the average value of their learning outcomes is 70.The problems in the research location are as follows: (a) the teaching and learning process in a class that is less varied, (b) the assumption that social studies is a collection of memorization material that is boring and reduces students' motivation to learn, and (c) the learning outcomes of students for social studies subjects are still low. This study followed a classroom action research design consisting of 4 activities, namely planning, acting, observing, and reflecting in which the data were presented in a descriptive qualitative manner. The results of the study of the application of the learning model of sending greetings and questions with BUS media went well according to the syntax, activity and learning outcomes increased. Classical completeness of the preliminary observations was 37%, Cycle I increased 74% and cycle II increased to 95%.